PEMANFAATAN MEDIA DARING SEBAGAI SARANA PENGEMBANGAN PRODUK UKM DESA CREWEK KECAMATAN KRADENAN KABUPATEN GROBOGAN - Betty Eliya Rokhmah (Riset Manajemen dan Akuntansi, 2015)
This study aims to determin the effect of online media use to increase product sales and market improvement for SMEs (Small Business Enterprises) at Crewek Village, Kradenan District, Grobogan Regency. The results showed a significant difference in the number of product sales and acceptance of SMEs after using online media as a means of promotion and sales of its products. In addition to improving the product, online media usage can improve SMEs market shares. The usage of social media, such as facebook and twitter, are very supportive to increase sales and market utilization. Keyword : online media, small business enterprises, product sales, market shares, income.